Eyewitness memory in the news can affect the strategic regulation of memory reporting. Issue 6 (3rd July 2022) - Butt, Muhammad Mussaffa; Colloff, Melissa F.; Magner, Elizabeth; Flowe, Heather D.
ABSTRACT: The public is increasingly exposed to news about eyewitness memory errors. This study draws from the strategic memory regulation framework [Goldsmith, M., Koriat, A., & Weinberg-Eliezer, A. (2002). Strategic regulation of grain size memory reporting. Journal of Experimental Psychology: General, 131 (1), 73–95. https://doi.org/10.1037/0096-3445.131.1.73] to make predictions about how eyewitness memory reporting is affected by exposure to such reports. In Experiment 1, participants ( n = 226) viewed a mock crime, were exposed to a fictitious news report about eyewitness memory accuracy (memory is accurate, memory is inaccurate, or a control condition), and then recalled the mock crime. Participants who read that eyewitness memory is inaccurate were less confident in their memory accuracy and reported less information about the mock crime compared to those in the other conditions. The specificity and accuracy of recall did not vary across conditions, however. In Experiment 2, participants ( n = 2, 491) watched a mock crime and were asked to identify the perpetrator from a simultaneous lineup. Participants who read that eyewitness memory is inaccurate evaluated their memory for the mock crime as relatively poorer but their lineup decisions did not differ compared to other participants. This suggests that news about eyewitness memory inaccuracy affects how people evaluate their memory capability, and differentially affects memory output depending on the memory task.